2014
DOI: 10.1177/0883073814531329
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns of Micro-RNAs 146a, 181a, and 155 in Subacute Sclerosing Panencephalitis

Abstract: Subacute sclerosing panencephalitis is caused by persistent brain infection of mutated virus, showing inflammation, neurodegeneration, and demyelination. Although many factors are emphasized in the pathogenesis of subacute sclerosing panencephalitis, the exact mechanism of neurodegeneration remains unknown. Micro-RNAs are small, noncoding RNAs that regulate gene expression at the posttranscriptional levels. Micro-RNAs are essential for normal immune system development; besides they are also implicated in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Recently, Yis et al described the induction of three miRNAs (miRNAs 146a, 181a, and 155) in peripheral blood mononuclear cells of patients with SSPE, with no prognostic significance [ 36 ]. We examined these miRNAs in our neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yis et al described the induction of three miRNAs (miRNAs 146a, 181a, and 155) in peripheral blood mononuclear cells of patients with SSPE, with no prognostic significance [ 36 ]. We examined these miRNAs in our neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miR-155 increased in activated B cells, T cells, and monocyte/macrophage [8]. In addition, the study had found that miR-155 exists in synovioblast and mononuclear cells in rheumatoid arthritis [9]. Therefore, miR-155 plays an important role in inducing inflammatory reaction and immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that the pattern of miR expression is modified following RSV infection of nasal epithelial cells (Inchley et al, 2015;Hasegawa et al, 2018), and PBMCs from children (Wang et al, 2017). Deregulated miR expression occurs in MeV-infected human neuroblastoma cells and PBMCs (Inchley et al, 2015;Yis et al, 2015;Naaman et al, 2017;Hasegawa et al, 2018), as well as in PBMCs from RSV-infected children (Wang et al, 2017). It is known that MeV persistence in neuroblastoma cells is assisted by the downregulation of CDK6, a component of cell cycle progression regulated by miRNA-124 (Riddell et al, 2007;Naaman et al, 2017;Griffin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%